2020
DOI: 10.22271/j.ento.2020.v8.i4c.8153
|View full text |Cite
|
Sign up to set email alerts
|

Bio-efficacy, persistence and residual toxicity of different insecticides against soybean leaf eating caterpillar Spodoptera litura (Fabricius) infesting soybean

Abstract: The investigations on bio-efficacy, persistence and residual toxicity of different insecticides viz., chlorantraniliprole 0.004 per cent, ethion 0.100 per cent, triazophos 0.050 per cent, indoxacarb 0.010 per cent, emamectin benzoate 0.001 per cent, quinalphos 0.050 per cent and profenophos 0.100 per cent against Spodoptera litura (Fabricius) infesting soybean were conducted at the Experimental Farm of Department of Agril. Entomology, College of Agriculture, Latur (MS) during Kharif 2015. The overall results e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…Followed by emamectin benzoate 5% SG 0.15 g/l, was found to be next best effective treatments, with least mean larval population of (0.51 larvae/plant), followed by mean damage severity of (2.19/plant), with the (79.87%) reduction over control and (7.28 t/ha) of grain yield was obtained, with percent yield increased over control of (102.22%). The present research trials almost similar with the findings of Nayaka et al, (2019) [16] , who found Chlorantraniliprole 18.5 SC, was found most effective insecticides in reduction of Spodoptera litura, larval population followed by, Emamectin benzoate 5 SG was found next best treatments, and also similar with the findings of Dabhi et al, (2020) [7] , who recorded the lowest larval population of Spodoptera litura in soybean field, which was treated by Chlorantraniliprole 18.5 SC with the mean larval population of (5.90 larvae/plant) followed by Emamectin benzoate 5SG (9.86 larvae/plant). Hardke et al, (2011) [13] , found the lowest infestation of Spodoptera frugiperda on maize was significantly reduced in plot treated with Chlorantraniliprole.…”
Section: And Fig 1)supporting
confidence: 92%
“…Followed by emamectin benzoate 5% SG 0.15 g/l, was found to be next best effective treatments, with least mean larval population of (0.51 larvae/plant), followed by mean damage severity of (2.19/plant), with the (79.87%) reduction over control and (7.28 t/ha) of grain yield was obtained, with percent yield increased over control of (102.22%). The present research trials almost similar with the findings of Nayaka et al, (2019) [16] , who found Chlorantraniliprole 18.5 SC, was found most effective insecticides in reduction of Spodoptera litura, larval population followed by, Emamectin benzoate 5 SG was found next best treatments, and also similar with the findings of Dabhi et al, (2020) [7] , who recorded the lowest larval population of Spodoptera litura in soybean field, which was treated by Chlorantraniliprole 18.5 SC with the mean larval population of (5.90 larvae/plant) followed by Emamectin benzoate 5SG (9.86 larvae/plant). Hardke et al, (2011) [13] , found the lowest infestation of Spodoptera frugiperda on maize was significantly reduced in plot treated with Chlorantraniliprole.…”
Section: And Fig 1)supporting
confidence: 92%